2021
DOI: 10.1177/0258042x21989924
|View full text |Cite
|
Sign up to set email alerts
|

Impact of University Website Usability on Satisfaction: A Structural Equation Modelling Approach

Abstract: One of the many ways through which the universities can communicate with students is through their website, which is considered as the face of the organization. It also represents the organization as a whole, its culture, value and vision. The current study aimed to check the usability of Gujarat Technological University’s website from students’ perspective and to find its association with satisfaction. The current study tried to address the gap in the literature, wherein in the Indian context, the majority st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Similar to previous studies, ease of website navigation was measured via the number of clicks to information on COVID-19 vaccines in English and in Spanish. 2,3 We also counted the number of clicks to access information on registration for a COVID-19 vaccine in Spanish. From each state's DPH website, we identified common "big-box" retailers distributing vaccines and recorded whether the main COVID-19 vaccine information page and appointment scheduling were available in Spanish on their website.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to previous studies, ease of website navigation was measured via the number of clicks to information on COVID-19 vaccines in English and in Spanish. 2,3 We also counted the number of clicks to access information on registration for a COVID-19 vaccine in Spanish. From each state's DPH website, we identified common "big-box" retailers distributing vaccines and recorded whether the main COVID-19 vaccine information page and appointment scheduling were available in Spanish on their website.…”
Section: Methodsmentioning
confidence: 99%
“…Karani et al [25] examined the usability of Gujarat Technological UW from the students' perspective and scrutinized its association with satisfaction. They found that all four dimensions of website usability were positively related to satisfaction.…”
Section: Indiamentioning
confidence: 99%
“…UWs had been well investigated for improvement of usability for all users in general [3,5,8,[10][11][13][14][15][16][17][18][19][20][21][22][23][24], such as students-lectures [4,13,25], people with disabilities [26], and even during the pandemic time [26][27][28][29]. However, there has been no holistic understanding and general trends based on the above literature on UW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, customer requirements, i.e. the quality features of products, are divided into three categories based on their asymmetric and nonlinear impact on end-user satisfaction and all three types of requirements are displayed in a two-dimensional diagram (Karani et al , 2021; Webb and Webb, 2004). The two dimensions are related to the good performance of a product or service and the level of customer satisfaction.…”
Section: Theoretical Foundationsmentioning
confidence: 99%